Discounting of Evolutionary Explanations in Sociology Textbooks and Curricula - Takács, Károly (Frontiers in Sociology, 2018)
Despite being internally fragmented by clashes of paradigms, sociology textbooks and introductory courses show a remarkable similarity in their content, while they share a peculiar neglect of small scale societies, non-human social relations, as well as evolutionary explanations. The mistreatment is explained by the strong position of sociology in the nature vs. nurture debate, by paradigmatic and ideologically motivated condemnations, by the later misuse of Social Darwinism, by certain unresolved issues of evolutionary explanations of human sociality, and by epistemological critiques of evolutionary explanations. The current study assesses the extent of this avoidance in sociology by three methods: a review of major sociology textbooks, a descriptive quantitative text analysis of introductory course outlines at top ranked universities, and a keyword search in the all-time most emblematic classical books in sociology. In reaction to this mistreatment, the benefits of synthesis of sociological explanations with evolutionary thinking are discussed.